Dokumentarzyści i krytyk. Zygmunt Kałużyński a dokumentaliści „nowej zmiany” - Jazdon, Mikołaj (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2017)
The article offers the analysis of how Zygmunt Kałużyński, the film critic of Polityka weekly magazine, described and stigmatized documentary films by Krzysztof Kieślowski, Tomasz Zygadło, Grzegorz Królikiewicz and Krzysztof Gradowski presented at the Cracow short film festival in 1971. Kałużyński criticized and mocked the aesthetics of the Polish “new wave” documentary cinema in a series of articles published in Spring and Summer of 1971. He presented films by brave and talented directors, contradicting the current social and political situation, as the unreflective imitation of the banal television documentary style based on in-front-of-the-camera interviews. The author compares Kałużyński’s proceedings to actions of a British journalist Robert Pitmann described by Tadeusz Różewicz in his essay A Journalist and the Poet. Pitmann conducted a sneering interview with T.S. Eliot for Sunday Express in 1958 and Różewicz comments on the possible effects of his text for its readers.